Robotic photogrammetric underwater inspection of hydropower plants - Ammann, Manuela (The International Hydrographic Review, 2025)
Manuela Ammann from the University of Applied Sciences Northwestern Switzerland is the winner of the IFHS Student Award 2023 for her Master’s thesis on “Robotic Photogrammetric Underwater Inspection of Hydropower Plants”. The following article summarises her award-winning work. Hydropower is th e most important domestic source of renewable energy in Switzerland, accounting for around 57 % of domestic electricity production. The high intensity usage of hydropower plants results in high costs for regular maintenance and inspection, which are currently carried out through manual inspections by professional divers. The aim of this work is to develop a workflow for underwater photogrammetry with Remotely Operated Vehicles (ROV) to supplement or replace these dangerous and expensive dives. A calibration frame was developed to provide a scale reference for the data collected during the inspection. With different acquisition missions, investigations on camera calibration and 3D reconstruction were performed. The reconstruction of underwater objects was successfully implemented. Well- distributed control points provide accurate results as a point cloud with a sub-centimetre accuracy at object distances of up to 6 m. 80 % of the point cloud differ less than 1 cm from the reference scan.